THE CHILDFREE PHENOMENON IN JAPAN: AN ANALYTICAL STUDY FROM A CONTEMPORARY ISLAMIC LEGAL PERSPECTIVE - Khanan Saputra; Noor Kholifah Hidayati (Universitas Islam Indonesia, 2025)
Purpose – This study aims to explore the childfree phenomenon prevalent in Japan. From year to year, Japan continues to experience a decline in birth rates, which makes it an interesting country to study. From the phenomenon occurring in Japan, the author also wants to find out how the childfree issue is becoming more widespread in Japan, how Islamic law responds to this issue, and how ethics views it. Methods – This research uses the literature study research method, so this research is complemented by various pre-existing sources and thus can strengthen the data. The research data were obtained from books, articles, and other writings related to the topic of the problem. Findings – Japan has experienced a decline in birth rates since the 1970s, which has been exacerbated by the emergence of the childfree trend among the younger generation. Economic factors are the reason many young people choose not to have children. In addition, philosophical views related to living a freer life without traditional pressures or social norms that demand a brilliant life, which creates its own burden, also influence this decision. In Islamic law, the practice of childfree by aborting a fetus after four months of pregnancy is prohibited. However, Islam itself is a religion that respects the sanctity of children, as children are the next generation who will become Khalifah on this earth. Research contribution/limitations – This study’s results provide insight into the childfree phenomenon that is rampant in Japan from the perspective of Islamic law. However, this research also has limitations, as the method used is limited to a literature study without going directly to the field. Originality/value – This research adds references related to childfree from the perspective of Islamic law, where childfree itself is a contemporary study whose practices have been rampant; therefore, Islamic law also offers answers.